Studies on formulation and optimization of gastro retentive multi-particulates of glibenclamide and metformin hydrochloride for the treatment of type II diabetes mellitus using gelucire: A review - Upadhyay P.; Pandit J.K.; Upadhyay S.; Ghosh A.K. (My University, 2025)
In order to increase the bioavailability of poorly soluble drug as well as highly soluble drug, the residence time of the orally administered dosage form in the upper GIT needs to be prolonged. Gelucire are used as carrier for designing low density floating drug delivery system. Glibenclamide is a low dose, poorly soluble drug with possible content uniformity problems and dissolution rate-limited bioavailability while Metformin HCl ranges from 0.5-2.5 gm per day divided in two or three doses taken with meals. Plasma half life is 1.7 -4.5 hrs and absolute bioavailability is 50-60%. There has been contradictory report on the utilization of metformin HCl in single unit gastroretentive dosage form.